ҚАРАҚАЛПАҚ ТЕАТРЫНЫҢ ПРОФЕССИОНАЛЛЫҚҚА ӨТИЎИНДЕ ДӘСЛЕПКИ АДЫМЛАР (1930-1939) - Пирназаров, С.М. (SCIENCE and SOCIETY, 2023)
This article is thoroughly studied the first steps in the transition of the Karakalpak theater to professionalism, the opening of the Karakalpak theater studio at GITIS and the behavior of the Karakalpak youth who studied there, Pijova and Bibikov’s dedication to the studio.